Implementation Of Point Of Sales Using Laravel Framework on Matahari Motor - Dea Erlinda Thendy Salim; David David; Gusti Syarifuddin; Sandy Kosasi; I Dewa Ayu Eka Yuliani (Universitas Raharja, 2023)
One of the developments in technology in the modern era is computers as a alternative for human labor. The development of advanced technology must also be balanced with the right application. Web application is one of them because it makes easier to access information on any device as long as it’s connected to the internet. This research aims to create a POS application that can help in facilitating more structured data management with the features provided. The method that this research used is Action Research. Website design using Prototype method, modeling in design using Unified Modeling Language (UML), and database modeling using Entity Relationship Diagram (ERD). Website development using the Laravel framework, and testing using the Black Box method with Equivalence Partioning. The results obtained from this study are the Live Search feature which helps in searching for item data, the notification feature for minimal stock so as not to be late in placing an order, Authentication Login using Jetstream Laravel, there are barcodes and print invoice to assist in the transaction process, error messages feedback or succesfull. successful, the calculation of the income reports, and this research was developed using the Model View Controller (MVC) concept architecture.